The Emerging Resistance in Nosocomial Urinary Tract Infections: From the Pediatrics Perspective - Devrim, Fatma (Mediterr J Hematol Infect Dis, 2018)
BACKGROUND: Healthcare-associated infections results in increased health care costs and mortality. There are limited studies concerning the distribution of the etiologic agents and the resistance patterns of the microorganisms causing healthcare-associated urinary tract infections (HA-UTI) in pediatric settings. OBJECTIVES: The aim of this study was to evaluate the distribution and antibiotic susceptibility patterns of pathogens causing HA-UTI in children. MATERIAL AND METHODS: Isolates from 138 children with UTI who were hospitalized in pediatric, neonatal and pediatric surgery intensive care units were reviewed. RESULTS: Most common isolated organism was Klebsiella pneumoniae (34.1%) and Escherichia coli (26.8%). Among the Pseudomonas aeruginosa, Meropenem and imipenem resistance rates were 46.2% and 38.5%. Extended-spectrum beta-lactamase (ESBL) production was present in 48 Klebsiella species (82.8%). Among ESBL positive Klebsiella species, the rate of meropenem and imipenem resistance was 18.8%, and ertapenem resistance was 45.9%. Extended spectrum beta-lactamase production was present in 27 (72.9%) Escherichia coli species. Among ESBL positive E. coli, the rate of meropenem and imipenem resistance was 7.4%, and ertapenem resistance was 14.8% CONCLUSIONS: Emerging meropenem resistance in P. aeruginosa, higher rates of ertapenem resistance in ESBL positive ones in E. coli and Klebsiella species in pediatric nosocomial UTI are important notifying signs for superbug infections.